PENGARUH STRATEGI PROMOSI FLASH SALE PADA SHOPEE TERHADAP KEINGINAN KONSUMEN UNTUK BERPARTISIPASI YANG DI MODERASI OLEH PERCEIVED CONTAGIOUSNESS OF MASS PARTICIPATION - Ambarwati, Ucik; Soepatini (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
The purpose of this research is to investigate the relationship between flash sale promotion strategies on shopee on consumer willingness to participate moderated by perceived contagiousness of mass participation. The choice of methodology in this researce are people who have the shopee application which was selected as a sample in this research, a total of 144 respodent. The date in this research comes from primary data through the range of measurements used, namely 5 Likert scales. The results of the analysis process in this study indicate that perceived temptation of price promotion, perceived fun of promotion, perceived category richness of promotion have a significant and positive influence on participation intention, but for perceived contagiousness of mass participation does not have a negative influence and no significance on participation intention. Then perceived contagiousness of mass participation does not moderate the relationship between perceived temptation of price promotion and perceived fun of promotion on participation intention, but moderates the relationship between perceived category richness of promotion on participation intention.